PENGARUH KBSIAPAN PEGAWAI DAN FAKTOR.FAKTOR SOSIAL TERHADAP NIAT MENGGUNAKAN SISTEM PERBBNDAHARAAN DAN ANGGARAN NEGARA (SPAN) DI DIREKTORAT JENDRAL PERBENDAHARAAN - , Latif Wahyono ([Yogyakarta] : Universitas Gadjah Mada, 2014)
State Treasury and Budget System (SPAN) is an integrated system that is planned to be implemented in the Directorate General of Treasury. A readiness factor of employee as the users of the system is one of the important issues in the implementation of the new system. This study aimed to examine the effect of employee readiness and social factors on the intention to use SPAN. This study combines the Technology Readiness Index (TRI) and the Technology Acceptance Model (TAM) in one model. This study also adds social factors of the Theory of Interpersonal Behavior. Respondents in this study were 127 employees at the Directorate General of Treasury who worked in the Treasury Office. SEM analysis of the data used PLS-based variant. Results of this study showed that each employee readiness dimensions, namely optimism, innovativeness, insecurity and discomfort have a different effect on the intention to use SPAN. And social factors have a significant positive effect on the intention to use SPAN.